SAFETY AND TRANSIENT ANALYSES FOR FULL CORE CONVERSION OF THE DALAT NUCLEAR RESEARCH REACTOR - LUONG , BA VIEN; LE , VINH VINH; HUYNH , TON NGHIEM; NGUYEN , KIEN CUONG (Nuclear Science and Technology, 2011)
Preparing for full core conversion of Dalat Nuclear Research Reactor, safety and transient analyses were carried out to confirm the ability to operate safely of proposed Low Enriched Uranium (LEU) working core. The initial LEU core consisting of 92 LEU fuel assemblies and 12 Beryllium rods was analyzed under initiating events of uncontrolled mwithdrawal of a control rod, cooling pump failure, earthquake and fuel cladding fail. Working LEU core’s response was evaluated under these initial events based on RELAP/MOD 3.2 computer code and other supported codes like ORIGEN, MCNP. Obtained results showed that safety of the reactor is maintained for all transients/accidents analyzed.